Seizure Outcome and Its Prognostic Predictors After Hemispherotomy in Children With Refractory Epilepsy in a Chinese Pediatric Epileptic Center - Ji, Taoyun; Liu, Ming; Wang, Shuang; Liu, Qingzhu; Wu, Ye; Zhang, Yuehua; Bao, Xinhua; Wang, Wen; Wang, Ruofan; Yu, Guojing; Liu, Xiaoyan; Cai, Lixin; et al. (Frontiers in Neurology, 2019)
Object: To explore the post-hemispherotomy seizure outcome and its prognostic predictors in children with refractory epilepsy. Methods: We reviewed 83 consecutive children patients with refractory epilepsy who underwent hemispherectomy from June 2014 to January 2017 at our Paediatric Epilepsy Centre. Demographic, clinical, EEG, neuroimaging, and surgical data were collected. Seizure outcome data were collected via outpatient clinics as well as telephone visits and were graded according to Engel criteria. Logistic regression model and Cox proportional hazard regression model were respectively applied to explore the related factors predicting the seizure outcomes of children after hemispherotomy. Results: Of the 83 patients, 55 (63.2%) were male. The mean seizure onset age was 1.9 years (0–8.7 years), and the mean surgery age was 5.0 years (0.8–14.0 years). At a mean follow-up of 3years, 69 children (83.1%) were seizure free, and 14 (16.9%)exhibited seizure recurrence. In a univariate analysis, whether or not considering follow-up time, a nonlateralized interictal EEG pattern, bilateral PET abnormalities and acute postoperative seizures (APOS) all could predict poor seizure outcome after hemispherotomy. Bilateral PET abnormalities were independently correlated with unfavourable seizure outcomes in the multivariate Logistic regression analysis (Odds ratio(OR)=13.05, 95%CI=1.52-112.29, P=0.019) and in the multivariate Cox proportional hazard analysis(OR=13.99, 95%CI=2.75-71.17, P=0.001). Conclusions: Children epileptic patients with bilateral PET abnormalities may have poor seizure outcomes after procedure of hemispherotomy. This study will facilitate better candidate selection for hemispherotomy and early identification of unfavourable seizure outcomes.